Ruptur Ureter Sinistra Pasca Histerektomi atas indikasi Adenomiosis Uteri dan Kista Endometrium - Ghania Alizar; Nabila Quinsy Chiqita; Rodiani - (Medula, 2023)
Adenomyosis is a benign gynecological disorder that invades endometrial tissue into the myometrial lining and suspected as one of the causes of subfertility in women. Adenomyosis usually diagnosed in the 4-5th decade of life, at the end of the reproductive period and perimenopause, but currently many women of reproductive age already suffer from adenomyosis, several studies suggest that this is influenced by lifestyle changes. A 45-year-old female patient was admitted to the emergency department with complaints of difficulty urinating after a hysterectomy 8 days before admission to the hospital for indications of adenomyosis and endometrial cysts. In the anamnesis, the patient complained of only a small amount of fluid coming out of the drainage and urinary catheter and 4 days before admission to the hospital there was no flow of urine coming out of the urinary catheter. This patient then underwent ureteroscopy and found signs of left 1/3 distal ureteral rupture. Operative management consists of neoimplantation and placement of a Double J stent in the left ureter. After 4 days postoperative, the patient was allowed to go home.